Pengaruh Kepemimpinan dan Komitmen Kerja terhadap Kinerja Karyawan di CV. Sentral Teknik Abadi - Eka Nurmelasari, Elyzabeth; Sonja Andarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of leadership and work commitment on employee performance CV. Sentral Teknik Abadi. The method used in this research is a quantitative type method. This study used a population of 47 employees of CV. Sentral Teknik Abadi and the sample of this study amounted to 47 employees of CV. Sentral Teknik Abadi. Based on the processed data, it was found that the sig value on the leadership variable (X1) is 0.000 < 0.05. The calculated t value is 4.943 > t table 2.015. Then, H0 is rejected and H1 is accepted, meaning that the leadership variable partially affects the performance of CV. Sentral Teknik Abadi employees. The sig value on the work commitment variable (X2) is 0.000 < 0.05. The t value is -4.032 < t table 2.015. Then, H2 is accepted, meaning that the work commitment variable has a partially negative effect on the performance of CV. Sentral Teknik Abadi employees.